Female Androgenetic Alopecia with Male Pattern Caused by an Androgen-Producing Tumor - Dueñas, Angelica Ruiz (Int J Trichology, 2020)
Female androgenetic alopecia (FAGA) is a common cause of hair loss in women. Typically, it is characterized by a reduction of hair density on biparietal and vertex regions of the scalp with preservation of the anterior hair implantation line. However, it can also appear with recession of the anterior hairline known as FAGA with male pattern (FAGA-M). In these cases, it is important to consider a state of hyperandrogenism and look for other signs such as hirsutism, acne, and menstrual irregularities. A sudden onset in a postmenopausal woman must make us suspicious of an androgen-secreting tumor. We present two cases of FAGA-M secondary to an ovarian tumor that was successfully resolved after surgical treatment.